Adding Value to Innovation: Impressionism and the Transformation of the Selection System in Visual Arts - Wijnberg, Nachoem M; Gemser, Gerda (Organization science (Providence, R.I.), 2000)
Valuation of cultural products tends to be problematic. In this paper, we provide insight into how valuation of cultural products takes place by describing the changing role and significance of different types of selection systems. Three basic types of selection systems are distinguished: market selection, peer selection, and expert selection. We show that the rise of a group of painters known as the Impressionists was facilitated by a change in the selection system of the visual arts industry from one dominated by peers into one dominated by experts. In the new selection system, innovativeness has become the most highly prized product characteristic, while a range of experts have begun to play an essential role, certifying the innovativeness of either individual artists or groups of artists.